Kepuasan Pelanggan Memediasi Kualitas Pelayanan dan Harga Terhadap Loyalitas Pelanggan - Dwi Gemina; Siti Robiatul Adawiyah; Yulianingsih Yulianingsih (Journal of Management and Bussines (JOMB), 2023)
This research aims to determine the direct influence, indirect influence and total influence of service quality and price on customer loyalty through customer satisfaction. The data analysis method uses path analysis and Sobel Test analysis via IBM SPPS Version 25.00. The results of the t test research show that the calculated t value for the service quality and price variables and the calculated t value for the variables are smaller than the sensitivity level (Sig.) < 0.05, meaning the model is significant. The F test shows that the calculated f value is smaller than the sensitivity level (Sig.) < 0.05. These two variables, namely service quality, price and customer satisfaction, have a sensitivity level value (Sig.) < 0.05, meaning the model is significant. In conclusion, customer satisfaction is able to mediate service quality and price partially or simultaneously on customer loyalty at the AHASS 1753 PT Workshop company. Kusuma Sejati Inti Prima. Keywords: Price, Customer Satisfaction, Service Quality, Customer Loyalty